Effect of the sprag wear on centrifugal disengagement overrunning clutches - LEI Yanbin; NING Fenglian; ZENG Zhuo; PENG Kai (Jixie chuandong)
ObjectiveIn order to understand the impact of sprag wear on the dynamic performance of clutches, a clutch model with sprag of localized wear was established based on the virtual prototype.MethodsThe dynamic characteristics of the model were simulated and analyzed by using Adams software. The influence of sprag wear on contact force between sprag and inner race, the torque on the input shaft, the difficulty of dynamic engagement, and the critical disengagement speed during overrunning were studied.ResultsThe results show that the simulation results of the disengagement speed of the virtual prototype have an error of less than 10% compared to the experimental results, which verifies the correctness of virtual prototype simulation; the contact force between the sprag and inner race, as well as the torque acting on the input shaft, decrease firstly and then increase with the increase of the sprag wear; the critical speed for the clutch to enter the fully overrunning state increases with the increase of the sprag wear.